Barriers to prosperity: Developing countries and the need for trade liberalisation - Sushil Mohan; Sangeeta Khorana; Homagni Choudhury (Institute of Economic Affairs (IEA), 2012)
Trade expert Sushil Mohan, in a paper published by the IEA, argues that non-tariff barriers are an important impediment to trade for less developed countries and need to be brought to the forefront of the trade debate.Non-tariff barriers are an important impediment to trade for less developed countries. Such barriers can be very high on both processed and unprocessed agricultural products. These barriers include:EU rules of origin and rules relating to traceability.The combination of these rules with preferential trade agreements which becomes more onerous as the degree of processing increases.Health and safety regulations.Labelling schemes such as fair trade and organic.Environmental standards, such as those relating to palm oil exports.Both export and import procedures imposed by developing countries themselves: for example, exporting in India involves 12 separate processes.Non-tariff barriers need to be brought to the forefront of the trade debate if developing countries are to move into the export of higher value added products.Currently, developing countries have a low share of exports of final processed products which normally have a higher value added than primary agricultural products. For example, developing countries account for 91 per cent of raw coffee exports but only 3 per cent of processed coffee exports.This situation is frequently blamed on developed countries applying trade barriers and escalating tariffs on processed commodities.However, there is little truth in this allegation, at least in relation to the important commodities of coffee, tea and cocoa. However, tariffs barriers do exist in relation to other commodities such as cotton, rice and so on.Not only are tariff barriers close to zero on coffee, tea and cocoa, there is also very little tariff escalation - that is the level of tariffs on processed products is not significantly greater than the level of tariffs on unprocessed products. Japan is the only major exception to this general pattern.On the other hand, tariff barriers between developing countries themselves can be very high. For example, tariffs on roasted coffee are 71 per cent in Mexico and 99 per cent in India. There is, however, little evidence of tariff escalation on trade between developing countries: tariffs are often very high on both processed and unprocessed agricultural products.There may well be important tariff barriers with regard to higher degrees of processing of more complex products (such as chocolate). These are especially prevalent in product lines where there is competition between developed and under-developed countries or where developed countries produce some of the ingredients for these products (for example, milk and sugar for chocolate).Non-tariff barriers are often home grown within developing countries themselves. The experience of trade reform suggests that the benefits from their removal will mainly flow to developing countries. Non-tariff barriers must therefore be a clear priority in future trade policy and in domestic policy making in poor countries.
Keywords: 330; Foreign agricultural trade; Trade liberalization; Non-tariff trade barriers; Developing countries; Agraraußenhandel; Handelsliberalisierung; Nichttarifäre Handelshemmnisse; Entwicklungsländer